The impact of foreign trade development on the organization of socio-economic security of Ukraine - Irena Svydruk; Orystlava Sydorchuk; Olha Trut; Mariana Myronova; Olha Klepanchuk (Nicolaus Copernicus University in Toruń, 2022)
The integral indicator and dynamics of Ukraine’s level of socio-economic security in the main areas in which it manifests are determined. The dynamics of the level of economic security depending on the development of the foreign trade of Ukraine are analysed using the official method for calculating Ukraine’s level of economic security. Hypotheses relating to the existence of relationships between indicators of the economic security of foreign trade and the general level of socio-economic security are studied in detail in terms of individual subsystems of socio-economic security. With the help of regression analysis, the hypotheses are statistically confirmed and the measures of the influence of parameters of economic security of foreign trade development on socio-economic security are revealed. The main opportunities and threats related to ensuring the socio-economic security of Ukraine in foreign trade development are identified. It is proposed to direct further research to developing institutional tools to create opportunities to strengthen the positive impact of foreign trade on ensuring the socio-economic security of Ukraine.
Keywords: socio-economic security; foreign trade; economic cooperation; institutional regulation; market; Ukraine